Project-Based Learning for Assemblr Edu Augmented Reality Media: Products and Experiences of Primary School Teacher Education Students - Fauziah, Nurul; Khusaini, Fakhri; Ummah, Rakhmatul (Journal of Authentic Research, 2026)
The development of digital technology requires prospective teachers to have the ability to design innovative, technology-based learning media. This study, involving 35 primary school teacher education students, aims to describe the implementation of Project-Based Learning (PjBL) in the development of Augmented Reality (AR)-based learning media using Assemblr Edu and to examine the products and learning experiences of the students. This study uses a qualitative descriptive approach with a case study design. The research subjects consisted of 35 primary school teacher education students taking the Learning Multimedia course. Data were collected through observation, interviews, and documentation of students’ AR products. Data analysis was carried out using the Miles, Huberman, and Saldaña model through the stages of data condensation, data display, and conclusion drawing. The results showed that the implementation of PjBL was carried out in a "very good" category with an implementation percentage of 89%, while the interview results indicated an increase in collaboration skills (90%), the development of digital technology skills (80%), and an increase in creativity (70%). The analysis of AR media products showed that students were able to develop media with good aspects of material suitability, visual design, and interactivity. This research practically contributes to the development of digital, collaborative, and creative competencies for prospective elementary school teachers through authentic project-based learning experiences. The research findings indicate that the application of Assemblr Edu AR-based PjBL provides authentic learning experiences that support the development of digital competencies, creativity, and the ability of primary school teacher education students to produce innovative learning media.